Dermal Phospho-Alpha-Synuclein Deposition in Patients With Parkinson's Disease and Mutation of the Glucocerebrosidase Gene - Doppler, Kathrin; Brockmann, Kathrin; Sedghi, Annahita; Wurster, Isabel; Volkmann, Jens; Oertel, Wolfgang H.; Sommer, Claudia (Frontiers in Neurology, 2018)
Heterozygous mutations in the glucocerebrosidase gene (GBA1) represent the most common genetic risk factor for Parkinson’s disease (PD) and are histopathologically associated with a widespread load of alpha-synuclein in the brain. Therefore, PD patients with GBA1 mutations are a cohort of high interest for clinical trials on disease-modifying therapies targeting alpha-synuclein. There is evidence that detection of phospho-alpha-synuclein (p-syn) in dermal nerve fibers might be a biomarker for the histopathological identification of PD patients even at premotor or very early stages of disease. It is so far unknown whether dermal p-syn deposition can also be found in PD patients with GBA1 mutations and may serve as a biomarker for PD in these patients. Skin biopsies of ten PD patients with different GBA1 mutations (six N370S, three E326K, one L444P) were analyzed by double-immunofluorescence labeling with anti-p-syn and anti-protein gene product 9.5 (PGP9.5, axonal marker) to detect intraaxonal p-syn deposition. Four biopsy sites (distal, proximal leg, paravertebral Th10 and C7) per patient were studied. P-syn was found in six patients (three N370S, three E326K). P-syn deposition was mainly detected in autonomic nerve fibers, but also in somatosensory fibers and was not restricted to a certain GBA1 mutation. In summary, dermal p-syn in PD patients with GBA1 mutations seems to offer a similar distribution and frequency as observed in patients without a known mutation. Skin biopsy may be suitable to study p-syn deposition in these patients or even to identify premotor patients with GBA1 mutations.